A Narrative Analysis: Application of Co-Cultural Theory to The Coming out Phenomenon of Indonesian LGBT - Adityaputri, Aurellia Nathania (Action Research Literate, 2024)
This study aims to determine the influence of culture on LGBT people's melela decision. In addition, the researcher also explores the application of co-cultural theory developed by Mark Orbe to the melela phenomenon, especially in the context of LGBT people in Indonesia. This research uses a qualitative approach with a narrative analysis method of 47 articles collected from the melela.org website. Researchers selected articles based on specific topics relevant to the research. The results of the research analysis show the dominance of cultural influences on the melela decision of LGBT people in Indonesia, also proving most of Orbe's claims, that to successfully survive in the midst of a dominant culture members of a co-cultural group will adopt one or more specific communication orientations in their daily interactions. In addition, the research also discusses the effect of melela on the quality of relationships and interpersonal communication of LGBT people with those closest to them, by analyzing their reactions